(untitled) (Journal of Universal Science Research, 2023)
In the last decade, among medical scientists and doctors all over the world, the interest in the problems of patients’ commitment to the treatment process is increasing, which is explained by the fact that the effectiveness of the treatment of most common chronic diseases is directly related not only to adequate treatment, but also to the level of patients’ adherence to the treatment process. Among the developed countries, according to the results of epidemiological studies conducted in our Republic, the prevalence rate of arterial hypertension (AG) among the population ranges from 20 to 40%, and taking into account the fact that this rate increases with age, it is necessary to improve the effectiveness of hypotensive treatment and support patients with hypertension. relevance arises. [5, ]. Research shows that only about 50% of patients with cardiovascular disease follow the doctor’s instructions [6]. It should be noted that a high level of adherence has a positive effect on the quality of life of patients and the course of the disease [7].